2018
DOI: 10.1016/j.anireprosci.2018.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental flaxseed modulates ovarian functions of weanling gilts via the action of selected fatty acids

Abstract: The aim of this study was to examine the influence of dietary flaxseed on the endocrine and ovarian functions of weanling gilts challenged with E. coli and Coronavirus infections treated with dietary probiotic cheeses and to understand the possible mechanisms of its effects on ovarian function. Probiotics were used as a natural substitution for antibiotics and 10% dietary flaxseed is an effective prebiotic which supports the action of probiotics and has other beneficial effects on the organism. Probiotics with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 38 publications
4
24
1
Order By: Relevance
“…It has been shown that a diet containing 5% flaxseed could delay puberty, whereas using a diet containing 1% flax seed could result in early maturity and increase ovarian weight as well as serum estrogen level [40]. Vlckova R et al showed that supplemental flaxseed modulates ovarian functions of weanling gilts via the action of selected fatty acids [41]. The previous studies have indicated that phytoestrogens, such as soy, red clover, and flaxseed, are effective in reducing serum estrogen levels and thus could decrease the severity of menopausal symptoms, such as flushing [42] Previous studies demonstrated that excessive consumption of phytoestrogens, such as soy, could negatively affect the genital system, destroy ovarian follicles, and decrease body weight and ovary [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a diet containing 5% flaxseed could delay puberty, whereas using a diet containing 1% flax seed could result in early maturity and increase ovarian weight as well as serum estrogen level [40]. Vlckova R et al showed that supplemental flaxseed modulates ovarian functions of weanling gilts via the action of selected fatty acids [41]. The previous studies have indicated that phytoestrogens, such as soy, red clover, and flaxseed, are effective in reducing serum estrogen levels and thus could decrease the severity of menopausal symptoms, such as flushing [42] Previous studies demonstrated that excessive consumption of phytoestrogens, such as soy, could negatively affect the genital system, destroy ovarian follicles, and decrease body weight and ovary [43].…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone (P4), estradiol-17β (E2), and insulin-like growth factor I (IGF-I) concentrations were analyzed in 25–100 µL of either blood serum or culture medium. Radioimmunoassay was used for P4 and E2 assessment (ng/mL and pg/mL, respectively) and immunoradiometric assay for IGF-I assessment (ng/mL) according to the manufacturer’s instructions in duplicate as described in our previous studies [ 27 , 28 ]. Values in the culture medium are expressed in ng (P4, IGF-I) or pg (E2) per mg tissue per day.…”
Section: Methodsmentioning
confidence: 99%
“…PUFA are the integral components of cell membranes influencing their physical-chemical properties and fluidity (Yu et al 2014). Phytoestrogens can stimulate lipid metabolism including PUFA, in the liver by favouring the metabolism of n-3 PUFA over n-6 PUFA (Sopková et al 2017;Vlčková et al 2018;Rezaei et al 2020). Decreased activity of Δ-6-desaturase, the enzyme common for metabolism of both n-6 and n-3 PUFA (Stoffel et al 2008), results in the incorporation of n-3 PUFA derivatives in membranes of all the body cells (Hulbert et al 2005) and in modulation of cell cycle and apoptosis (Vlčková et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoestrogens can stimulate lipid metabolism including PUFA, in the liver by favouring the metabolism of n-3 PUFA over n-6 PUFA (Sopková et al 2017;Vlčková et al 2018;Rezaei et al 2020). Decreased activity of Δ-6-desaturase, the enzyme common for metabolism of both n-6 and n-3 PUFA (Stoffel et al 2008), results in the incorporation of n-3 PUFA derivatives in membranes of all the body cells (Hulbert et al 2005) and in modulation of cell cycle and apoptosis (Vlčková et al 2018). Many studies reported that flaxseeds are applicable in the suppression of menopausal symptoms (Akhbari Torkestani et al 2011;Colli et al 2012) and cancers of reproductive organs and breasts in postmenopausal women (Thompson et al 2005;Lowcock et al 2013;Cetisli et al 2015).…”
Section: Introductionmentioning
confidence: 99%